Pola Komunikasi Interpersonal Orang Tua Untuk Membentuk Kepribadian Da’i Pada Anak Didalam Keluarga Syaikh Muhammad Ismail - Nik Amul Lia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Da'wah activities will never succeed without a da'i. While the success or failure of a da'wah is largely determined by the personality of the da'i. However, the personality of the da'i does not necessarily appear by itself but requires a long process, so if parents want to shape the personality of the da'i in their child, a certain pattern of interpersonal communication is needed to instill Islamic values in the child's personality. In terms of forming the personality of the da'i in children, the pair of shaykhs Muhammad Ismail and Shafiyyah have succeeded in making their three sons become preachers who not only have good personalities but can also preach and make changes to Indian society, one of which is Shaykh Muhammad Ilyas Al-Kandalawi. The purpose of this study was to determine the pattern of interpersonal communication between Shaykh Muhammad Ismail and Shafiyyah in shaping the personality of the preacher to Shaykh Muhammad Ilyas Al-Kandahlawi. The research method is library research or library research with a historical or heuristic approach and the type of research is life story. The results of the study are interpersonal communication patterns to shape the personality of the preacher, namely using the response and interactional stimulus model in the childhood phase by using the da'wah bil hal and discussion and media methods such as through books, real actions and observing the surrounding environment with the aim that Shaykh Muhammad Ilyas likes to practice -practice sunnah, expert worship, put the interests of others, intimacy and generosity, istiqomah, proud of Islam, and have anxiety about the condition of the people. Furthermore, the pattern of interpersonal communication in the maturity phase, the model used is interactional with the da'wah discussion method or mujilah which aims to develop the personality of the da'i in terms of struggling to spread Islamic teachings. Meanwhile, the discussion method was chosen to develop the creativity of Shaykh Muhammad Ilyas in finding, making and determining a particular da'wah method to overcome religious problems that occurred in his environment.